Some problems of the writing process in foreign language teaching - Krzemińska, Katarzyna (Glottodidactica, 2010)
The aim of this article is to stress the role and history of the writing skills in foreign languages teaching. The article attempts to present the definition of a skill in writing and to describe the process of writing in teaching a foreign language. Its main purpose is to show the process of text production as a way of communication between partners when they use the same codes.